EXITUS-UL REPREZENTAŢIONAL: CÂND, CUM, DE CE? - USM ADMIN (Moldova State University, 2011)
A thorough analysis of the literary resources shows that social representations as " structured ensembles of values, notions and practices relative to the objects of the environment", "images of people and events perceived by the groups" or as "mechanisms that ensure the connection to different explicative systems" are ultimately bound to die. Conveying a natural thing (or, as it is well-known, organizing life by systems of entities has not only a beginning but an end too), the exitus doesn't happen on its own but rather as a result of the implication of certain factors. Generally speaking, these are specific situations in which, on one hand, the group (=the bearer of the representation) is not what "it used to be" anymore (it has substantially changed its composition, it has isolated itself from the rest of the world, it doesn't see in the object of representation any value of social stake etc.) and on the other hand the object of representation ceases to express a polymorphic reality that could be activated for the individuals. Essentially the disappearance of some social representations constitutes a good premise for the emergence of other social representations. In the light of history and anthropology, this type of mental constructs, S.Moscovici's expression, "lead a life of their own, communicating with each other, opposing and changing harmoniously, disappearing only to emerge later under new garments".